(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
How does a person perceive forced self-isolation in general and within him/herself? This article presents a qualitative analysis based on twelve interviews with people in palliative care. The study was based on the existentialist perspective and phenomenological method and concluded that people build strategies to face illness and death from their life trajectory, as they understand the realisation of their ’project of being’.